Customer knowledge creation capability and performance in sales teams - USLU, AYPAR (SPRINGER, 2013)
Drawing on substitutes for leadership theory, this study examines the relationship between a sales team manager's empowering leadership and his or her sales team's customer knowledge creation capability. The authors develop and test a model that positions task interdependence, outcome interdependence, and their interactions as substitutes for empowering leadership. Further, the authors explore two perspectives of team-level performance-customer relationship performance and financial performance-as consequences of a sales team's customer knowledge creation capability. Using matched data collected from sales team managers and sales team members, the authors find general support for their hypotheses. The study finds that a sales manager's empowering leadership has a positive effect on a sales team's customer knowledge creation capability. However, the results also suggest that the positive effect of empowering leadership on a sales team's customer knowledge creation capability is mitigated when either outcome interdependence or both task and outcome interdependence are high. Further, as outcome interdependence and the interaction between task and outcome interdependence increases, a sales team's customer knowledge creation capability also increases, which suggests that outcome interdependence and the combination of task and outcome interdependence replaces the role of empowering leadership. The study also finds that the greater a sales team's customer knowledge creation capability is, the higher its customer relationship performance and sales team financial performance will be. Implications for customer knowledge creation in sales teams in the presence and absence of empowering leadership are discussed.
Keywords: Substitutes for leadership theory; Sales teams; Empowering leadership; Task interdependence; Outcome interdependence; Customer knowledge creation; Team performance; PRODUCT DEVELOPMENT TEAMS; HIGH-TECHNOLOGY FIRMS; LEADERSHIP SUBSTITUTES; EMPOWERING LEADERSHIP; EMPIRICAL-EXAMINATION; ORGANIZATIONS; MODERATOR; IMPACT; INTERDEPENDENCE; COOPERATION